Reduced soil tillage and insecticide use in pollen beetle management on oilseed rape in Finland - Ketola, Jarmo; Johansson, Annika; Träskman, Sonja; Hurme, Timo; Ojanen, Hannu; Himanen, Sari (Scientific Agricultural Society of Finland, 2026)
Brassica oilseeds are important protein crops for Nordic agriculture. Oilseed production is challenged by multiple insect pests, most importantly the pollen beetle (Brassicogethes aeneus). Concerns about pyrethroid resistance and potential harm to beneficial insects demands seeking for alternatives to synthetic insecticides. Conservation biological control through supporting natural enemies is a promising option for pollen beetle management. Here, four soil tillage strategies were applied with and without insecticide (pyrethroid tau-fluvalinate) to oilseed rape (Brassica napus L.) grown over three years in South-Western Finland to investigate the effect of different management strategies on the number of pollen beetle and its key natural enemies, oilseed rape yield and economic profitability. The use of tau-fluvalinate was not detrimental for parasitic wasp activity, but there was variability in their response to tau-fluvalinate treatment by cultivation strategy and year. However, tau-fluvalinate combined with repeated heavy soil management increased the number of pollen beetles, indicating disrupted dynamics between pollen beetles and their natural enemies. Importantly, economic profitability was sustained without insecticide inputs when soil cultivation was minimized.
Keywords: biological control; Brassica napus L.; Brassicogethes aeneus; parasitic wasps; profitability; soil cultivation